2017
DOI: 10.1016/s1473-3099(17)30252-9
|View full text |Cite
|
Sign up to set email alerts
|

Year-round influenza immunisation during pregnancy in Nepal: a phase 4, randomised, placebo-controlled trial

Abstract: Summary Background Influenza immunisation during pregnancy is recommended but not widely implemented in some low-income regions. We assessed the safety and efficacy in mothers and infants of year-round maternal influenza immunisation in Nepal, where influenza viruses circulate throughout the year. Methods In this phase 4, randomised, placebo-controlled trial, we enrolled two consecutive sequential annual cohorts of pregnant women from the Sarlahi district in southern Nepal. We randomised mothers 1:1 to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
238
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(262 citation statements)
references
References 28 publications
6
238
1
1
Order By: Relevance
“…2224 , 28 Corroborating the 63% (95% CI: 8–85%) efficacy against influenza-confirmed illness reported in Bangladesh in infants <6 months of age; the point vaccine efficacy estimates in subsequent RCTs was 49% (95% CI: 12–70%) in South African HIV-unexposed infants, 33% (95% CI: 4–54%) in Mali and 30% (95% CI: 5–48%) in Nepal. A meta-analysis of these four RCTs yielded an overall vaccine efficacy of 36% (95% CI: 22–48%) in protection of young infants against influenza confirmed illness following maternal IIV vaccination.…”
Section: Maternal Influenza Vaccinationmentioning
confidence: 93%
See 3 more Smart Citations
“…2224 , 28 Corroborating the 63% (95% CI: 8–85%) efficacy against influenza-confirmed illness reported in Bangladesh in infants <6 months of age; the point vaccine efficacy estimates in subsequent RCTs was 49% (95% CI: 12–70%) in South African HIV-unexposed infants, 33% (95% CI: 4–54%) in Mali and 30% (95% CI: 5–48%) in Nepal. A meta-analysis of these four RCTs yielded an overall vaccine efficacy of 36% (95% CI: 22–48%) in protection of young infants against influenza confirmed illness following maternal IIV vaccination.…”
Section: Maternal Influenza Vaccinationmentioning
confidence: 93%
“…Among the women, the initial study from Bangladesh which provided pneumococcal polysaccharide vaccine to the control arm reported a 36% (95% CI: 4–57%) reduction in acute febrile respiratory illness in IIV-recipients; findings which were replicated in the subsequent trial in Nepal (19%; 95% CI: 1–34% reduction]. 22 , 28 In contrast the RCTs in South Africa and Mali did not observe efficacy against all-cause influenza-like-illness, but, reported significant efficacy against influenza-confirmed (PCR detected) illness in the women (50%; 95% CI: 15–71% and 70%; 95% CI: 42–86%; respectively) 23 , 24 ; whilst in Nepal a non-significant effect was report for this outcome (31%; 95% CI: -10-56%).…”
Section: Maternal Influenza Vaccinationmentioning
confidence: 97%
See 2 more Smart Citations
“…In the South African placebo-controlled trial, vaccine efficacy against confirmed influenza was approximately 50% both in mothers and infants [60]. In Nepal, yearround maternal influenza immunization significantly reduced maternal influenza-like illness, influenza in infants and low birth weight, suggesting that this strategy could be useful in subtropical regions where influenza is present for many months [61]. Regarding safety, IIV did not increase risk of foetal death, spontaneous abortion or congenital malformations [59][60][61][62].…”
Section: Influenzamentioning
confidence: 98%